The historical imagology: subject and object of perception: Историческая имагология: субъект и объект восприятия - Uriadova, Anna (Przegląd Wschodnioeuropejski, 2020)
The article discusses historical imagology one of the areas of imagology in general. It analyzes the sources, which are essential and most often used in such studies. The historiography of the issue is briefly considered. This article for the first time in the research literature on historical imagology and imagology in general pays special attention to the object and subject of historical imagological works. Several approaches to determining the object of research have been identified. The subject of imagological research is examined in detail. The issue of factors affecting perception is raised. Attention is paid to the problem of image variability and stereotepization.